2021
DOI: 10.1016/s0140-6736(21)02758-6
|View full text |Cite|
|
Sign up to set email alerts
|

Omicron SARS-CoV-2 variant: a new chapter in the COVID-19 pandemic

Abstract: On Nov 25, 2021, about 23 months since the first reported case of COVID-19 and after a global estimated 260 million cases and 5•2 million deaths, 1 a new SARS-CoV-2 variant of concern (VoC), omicron, 2 was reported. Omicron emerged in a COVID-19-weary world in which anger and frustration with the pandemic are rife amid widespread negative impacts on social, mental, and economic wellbeing. Although previous VoCs emerged in a world in which natural immunity from COVID-19 infections was common, this fifth VoC has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
1,146
1
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,249 publications
(1,172 citation statements)
references
References 15 publications
14
1,146
1
11
Order By: Relevance
“…This variant contains >30 spike protein amino acid mutations that possibly are associated with increased transmissibility, severity, and capacity for immune escape [ [4] , [5] , [6] ]. It has been found that Omicron variant may lead to more significant escape from immune protection elicited by previous SARS-CoV-2 infection and perhaps even by existing Coronavirus disease 2019 (COVID-19) vaccines [ [7] , [8] , [9] , [10] ]. Thus, Omicron was designated as variant of concern (VOC), by the World Health Organization (WHO) on November 26th, 2021 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This variant contains >30 spike protein amino acid mutations that possibly are associated with increased transmissibility, severity, and capacity for immune escape [ [4] , [5] , [6] ]. It has been found that Omicron variant may lead to more significant escape from immune protection elicited by previous SARS-CoV-2 infection and perhaps even by existing Coronavirus disease 2019 (COVID-19) vaccines [ [7] , [8] , [9] , [10] ]. Thus, Omicron was designated as variant of concern (VOC), by the World Health Organization (WHO) on November 26th, 2021 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…These amino acid substitutions occur in the Receptor Binding Domain (RBD). Interestingly, this variant carries mutations found in other variants of concern (VOC); it has the deletion at spike position 69–70, similar to the Alpha variant that leads to the S gene dropout or S gene target failure [ 8 ]. It also has three key mutations similar to those found in Beta and Gamma variants that confer immune escape [ 8 ].…”
mentioning
confidence: 99%
“…Interestingly, this variant carries mutations found in other variants of concern (VOC); it has the deletion at spike position 69–70, similar to the Alpha variant that leads to the S gene dropout or S gene target failure [ 8 ]. It also has three key mutations similar to those found in Beta and Gamma variants that confer immune escape [ 8 ]. Additionally, it has a range of close mutations to the furin cleavage site similar to those present in the Delta variant [ 8 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations